Robert B. Parker's, Sunny Randall : Payback - Book 9 - Lupica, Mike; Parker, Robert B., 1932-2010 (New York : G. P. Putnams Sons, 2022)
"PI Sunny Randall has often relied on the help of her best friend Spike in times of need. When Spikes restaurant is taken over under a predatory loan agreement, Sunny has a chance to return a favor. She begins digging into the life of the hedge fund manager who screwed Spike over--surely a guy that smarmy has a skeleton or tow in his closet--and soon finds this new enemy may have the backing of even badder criminals. At the same time, Sunnys cop contact Lee Farrell asks her to intervene with his niece, a college student who reported being the victim of a crime but seems to know more than she is telling police. As the uncooperative young woman becomes outright hostile, Sunny runs up against a wall that shes only more determined to scale. Then, what appear to be two disparate cases are united by a common factor, and then the picture becomes ever more muddled. But one thing is clear: Sunny has been poking a hornets nest from two sides, and all hell is about to break loose." -- Back cover.
Keywords: Randall, Sunny -- (Fictitious character) -- Fiction; Women private investigators -- Fiction; Women college students -- Crimes against; Fiction; Sex crimes -- Fiction; Best friends -- Fiction; Boston (Mass.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction